2020
DOI: 10.1111/jcpe.13260
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of osteotome sinus floor elevation with or without bone grafting: The 10‐year results of a randomized controlled trial

Abstract: Shu-jiao Qian and Jia-ji Mo are contributed equally as co-first authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 36 publications
1
49
0
Order By: Relevance
“…Therefore, the 10-year cumulative survival rate of short implants was 90.7%, and the 10-year cumulative survival rate of conventional implants was 95.0%. However, there was no significant difference between the short implants and conventional implants [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the 10-year cumulative survival rate of short implants was 90.7%, and the 10-year cumulative survival rate of conventional implants was 95.0%. However, there was no significant difference between the short implants and conventional implants [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the 10-year cumulative survival rate of short implants was 90.7%, and the 10-year cumulative survival rate of conventional implants was 95.0%. However, there was no significant difference between the short implants and conventional implants [28]. Fugazzotto PA. (2017) reported that the 10-year success rate of short implants was 98.8%, and the 10-year success rate of conventional implants was 100% [19].…”
Section: Long-term Clinical Outcomementioning
confidence: 90%
See 1 more Smart Citation
“…The details of radiographic measurements have been previously described (Qian et al, 2020). A paralleling technique with a Rinn film holder (XCP Instruments; Rinn Corporation Elgin, Elgin, IL, USA) was conducted.…”
Section: Radiographic Outcomesmentioning
confidence: 99%
“…Autologous bone or different types of bone substitutes have been used in OSFE to maintain the space for better outcomes according to the previous studies [10,12,13]. However, many studies investigated that no significant differences in clinical and histological outcomes were found whether grafting material was used or not [9,11,[14][15][16][17]. Researchers indicate that grafting material utilization was not a prerequisite in the sinus floor elevation surgery regarding the osteogenic capability of the bony walls and Schneiderian membrane as well as the maintenance of endo-sinus space around implants beneath the elevated membrane [18,19].…”
Section: Introductionmentioning
confidence: 99%